If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 1) = 12x + 3 + -4x + 1 Reorder the terms: 4(1 + 2x) = 12x + 3 + -4x + 1 (1 * 4 + 2x * 4) = 12x + 3 + -4x + 1 (4 + 8x) = 12x + 3 + -4x + 1 Reorder the terms: 4 + 8x = 3 + 1 + 12x + -4x Combine like terms: 3 + 1 = 4 4 + 8x = 4 + 12x + -4x Combine like terms: 12x + -4x = 8x 4 + 8x = 4 + 8x Add '-4' to each side of the equation. 4 + -4 + 8x = 4 + -4 + 8x Combine like terms: 4 + -4 = 0 0 + 8x = 4 + -4 + 8x 8x = 4 + -4 + 8x Combine like terms: 4 + -4 = 0 8x = 0 + 8x 8x = 8x Add '-8x' to each side of the equation. 8x + -8x = 8x + -8x Combine like terms: 8x + -8x = 0 0 = 8x + -8x Combine like terms: 8x + -8x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -8x+9=-23 | | -4(x+3)+2x= | | 0.12x+0.3(x-1)=0.01(4x-2) | | x(x+1)(x+2)=21 | | 5x+15x-5=5(4x+6) | | 8+4n=9n-7 | | 24=7x-5-4x | | (sinx)2=0.5 | | -4+1-5m+m=m+2 | | 9(x+8)+2=38 | | 6(r-6)=-66 | | 8x(2n+3x)=10 | | 21n^2+14n+7=6n+11 | | -(4-5z)-2(-3z+4)-3z=-2(6-4z-8(1-z)) | | 5(3-5n)=65 | | 21n^2+8-4=6n+11 | | 5+6-3x=-4 | | 5a-10b=45 | | 4x+89=6x+109 | | 21n^2+8-4= | | 15-2y=15+3y | | X^2-2ax=6ab-3bx | | 5(s-1)=94-2(s-4) | | 4x-5+6=45 | | 20x=280 | | x^3-31x-30=0 | | 3a+b=54 | | -3(2y-4)-6= | | (5p-3p)=2p+9 | | 16x-13=7x+32 | | 2z^2+19-10=0 | | 4.9=4t+(-7t) |